The AIMS impact, 10 years on: internationalisation at home of ASEAN higher education institutions - Yazrina Yahya; Doria Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Internationalisation has been infused into the core activities of higher education institutions in ASEAN for the past 15 years. Various efforts have been taken to ensure that internationalisation is infused into the higher learning institutions. The efforts are impart through collaborations between the higher learning institutions with various organisations and associations such as ASEAN University Network (AUN), The ASEAN International Mobility for Students (AIMS), Support for Higher Education in ASEAN (SHARE) and various others. AIMS is a regional mobility programme designed with the objective of encouraging regional mobility among students and staff of ASEAN higher education institutions (HEIs), consequently support and accelerate ASEAN’s vision of an integrated community. The objective of the paper is to review the impact of the programme on participating HEIs, 10 years after it is implemented in the Southeast Asian region. It is argued that the biggest impact of AIMS is the introduction of the internationalisation concept to ASEAN HEIs. Participating HEIs benefit through internationalisation of curriculum, where they incorporate international, intercultural, and/or global dimensions into the content of the curriculum. Their student and staff population also experience development of intercultural competencies through various on-campus integration programmes introduced. Above all, the overarching intention of organising AIMS is to stimulate internationalisation at home among the ASEAN HEIs. Each initiative has to be ‘by design’; in other words, through deliberate design and planning, in order to benefit the overall campus community.